Approximate Analytical Methods For Ordinary Differential Equations Of Fractional Order - Alkresheh, Hytham Awad Hamad (2017)
In this study, the focus is on approximate analytical methods. These methods include: Adomian decomposition method (ADM), fractional differential transform method (FDTM), homotopy analysis method (HAM) and variational iteration method (VIM). The main objective of this thesis is to develop, analyse and apply these methods to find the analytical approximate solutions for some cases of linear and nonlinear ordinary FDEs.